The unspoken facets of buying by individual investors in Indian stock market. (12th August 2019) - Bondia, Ripsy; Biswal, Pratap Chandra; Panda, Abinash
Abstract : Purpose: The purpose of this paper is to develop an in-depth contextualized understanding of individual investors' buying decision in Indian stock market. Specifically, it provides answers to: how do individual investors make buying decision in stock market; and how and when do biases set in during such decisions. The paper also brings forward some aspects of individual's journey as an investor. Design/methodology/approach: Given the exploratory nature of this study, the paper takes a step away from typically used variance approach and instead uses a process approach. The authors do in-depth one-on-one interview, where each respondent shares his/her lived experiences as an investor retrospectively. To understand buying decision, each respondent is asked to elaborate three significant buying transactions carried out by him/ her in stock market. Findings: Socio-cultural factors are found to have significant influence in inducing respondents to enter market. "Safe" vs "Risky" mental account emerges as the prominent stock categorization done by Indian investors. Three building blocks, namely, Identification, Rationalization and Further Validation emerge as the building blocks that culminate into buying decision of individual investors. The biases are seen to play a dual role in such decisions; as Attention Boosters and Rationales. Originality/value: This study, to the best of authors' knowledge, is first of its kind which amalgamates behavioral biases with phenomenon such as attention and Rationalization, to understand "how" behavioral biases set in during buying decision of individual investors.